All the light that we can see: a new era in miniaturized microscopy. (January 2019) - Aharoni, Daniel; Khakh, Baljit; Silva, Alcino; Golshani, Peyman
One major challenge in neuroscience is to uncover how defined neural circuits in the brain encode, store, modify, and retrieve information. Meeting this challenge comprehensively requires tools capable of recording and manipulating the activity of intact neural networks in naturally behaving animals. Head-mounted miniature microscopes are emerging as a key tool to address this challenge. Here we discuss recent work leading to the miniaturization of neural imaging tools, the current state of the art in this field, and the importance and necessity of open-source options. We finish with a discussion on what the future may hold for miniature microscopy.